Local Building Regulators’ Institutionalised Behaviour Towards Mass Customised Housing (MCH) - Hamzah, Hasniyati; Mislam, Suzila (International Journal of Property Sciences (E-ISSN: 2229-8568), 2017)
Mass Customised Housing (MCH) is an innovation in house production that could potentially transform developers’ business models due to its buyer-friendly template by offering customised houses that can fulfil part or most of buyer’s housing requirements at reasonable prices, thus securing customer loyalty and market share in the long run. Thus far, the body of literature on MCH only focuses either on the technical or the financial side of MCH implementation, with a discernible lacuna in the regulatory response. A broad institutional approach frames this study whereby a questionnaire survey with close and open ended questions was conducted on local building regulators to examine their attitude towards MCH and to explore potential issues pertaining to MCH implementation. A total of 133 questionnaires were sent to building regulators in Peninsular Malaysia, with a response rate of 28.6%. Quantitative data was analysed to yield descriptive statistics whilst qualitative data was analysed based on thematic analysis. Quantitative results showed a strong positive acceptance of MCH within the current regulatory environment, yet qualitative findings revealed respondents’ concerns about stakeholders’ disconnect, MCH’s compatibility with the current system and development actors’ actual motivations. Findings give an insight into the attitude of local building regulators in balancing their statutory roles with furthering developers’ economic objectives and house buyers’ social objectives.